Method for degrading quinolone antibiotics in water body and detection
Patent Information
- Application Number
- CN202611200207.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-08-10
AI Technical Summary
[0006]本申请提供一种水体中喹诺酮类抗生素降解的方法,旨在解决现有喹诺酮类抗生素水污染治理技术中存在的催化剂活性低、适用pH范围窄、降解耗时久、材料稳定性差、组分易团聚、工艺复杂等技术问题
(1)本申请成功制备了棒状、颗粒状两种形貌可控的Sm2O3纳米材料,结合水热法高结晶度、共沉淀法高比表面积的双重优势,所得Sm2O3纳米材料结构稳定、缺陷位点丰富。一方面,Sm2O3可为其他活性组分提供优良的负载基底,另一方面, Sm2O3同时也作为活性组分,通过与Co、Al双金属氧化物复合改性,构建了稀土-过渡金属多组分协同催化界面,各活性组分之间充分发挥协同效应,大幅提升过一硫酸盐活化能力。
Smart Images

Figure CN122702446B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of water pollution treatment, specifically relating to a method for the degradation and detection of trace amounts of quinolone antibiotics in water. Background Technology
[0002] Antibiotics, with their excellent antibacterial properties and relatively low toxicity, are widely used in clinical medicine, livestock and poultry farming, aquaculture, and many other fields. However, due to the limited adsorption and metabolic capacity of organisms for antibiotics, most antibiotics cannot be completely degraded and are excreted in their original form or as metabolic intermediates in human and animal waste, ultimately entering the soil, surface water, and even groundwater environment. Residual antibiotic pollutants in various aquatic media can have significant toxic effects on the growth, metabolism, and physiological development of aquatic microorganisms, plants, and animals, triggering a series of aquatic ecological risks.
[0003] Currently, water pollution control technologies for antibiotics are mainly divided into two categories: conventional treatment technologies and advanced treatment technologies. Among them, traditional physical, chemical, and biological conventional water treatment technologies such as coagulation sedimentation and activated sludge processes are the mainstream wastewater treatment processes, but they have significant shortcomings in antibiotic removal. Coagulation and flocculation processes have extremely low removal efficiency for highly polar, small-molecule antibiotic pollutants; biological treatment processes are easily constrained by environmental conditions such as water temperature, water quality, and microbial community structure, making it difficult to effectively remove low concentrations of residual antibiotics in water and failing to meet the requirements for advanced water purification.
[0004] Peroxymonosulfate (PMS)-mediated Fenton-like advanced oxidation processes have become a cutting-edge and popular technology in the field of water environment and wastewater treatment due to their outstanding advantages of convenient operation and high pollutant degradation efficiency, providing a new solution for the treatment of persistent antibiotic pollution. PMS generates sulfate radicals (SO4•-) with an oxidation potential of 2.5–3.1 V through the breaking of peroxy bonds, exhibiting extremely strong oxidative degradation capabilities. Compared to traditional hydrogen peroxide-based oxidation processes, PMS has more diverse activation methods, achieving efficient activation through thermal activation, alkaline regulation, and transition metal catalysis. Among these, transition metal catalysis activation, due to its high efficiency, economy, and ease of implementation, has become the most widely studied activation method; cobalt, iron, and copper, among other transition metals, can effectively activate PMS. Activated PMS can simultaneously generate sulfate radicals and hydroxyl radicals (•OH), efficiently decomposing recalcitrant persistent organic pollutants in water through strong oxidation, making it a highly promising technology for treating antibiotic micro-pollution in water bodies.
[0005] However, existing Fenton-like advanced oxidation processes based on peroxymonosulfate (PMS) have technical drawbacks when treating quinolone antibiotic-contaminated water, including low catalyst activity, narrow applicable pH range, long degradation time, poor material stability, easy component aggregation, and complex process. Summary of the Invention
[0006] This application provides a method for the degradation of quinolone antibiotics in water, aiming to solve the technical problems existing in the treatment of water pollution by quinolone antibiotics, such as low catalyst activity, narrow applicable pH range, long degradation time, poor material stability, easy agglomeration of components, and complex process.
[0007] A method for preparing a nanocomposite catalyst for degrading quinolone antibiotics in water, comprising: (1) Sm2O3 nanorods Sm2O3-NR were prepared by hydrothermal method or Sm2O3 nanoparticles Sm2O3-NP were prepared by oxalic acid coprecipitation method; (2) The obtained Sm2O3-NR or Sm2O3-NP was redispersed in water to obtain Sm2O3-NR dispersion or Sm2O3-NP dispersion, respectively; the precipitant and the substance containing Co were also redispersed in water. 2+ Ions and Al 3+ The metal salt solution of the ion was simultaneously added dropwise to the Sm2O3-NR dispersion or the Sm2O3-NP dispersion, and the pH of the reaction system was controlled to be 8.5~9.5. After the addition was completed, the reaction system was aged in a water bath at 55~65℃ for 2~4 hours. (3) The reaction system after aging is centrifuged, washed with water until neutral, and dried in sequence, and then calcined in air to obtain nanocomposite catalysts Co3O4 / Al2O3 / Sm2O3-NR or Co3O4 / Al2O3 / Sm2O3-NP.
[0008] This application aims to provide a Co3O4 / Al2O3 / Sm2O3 composite nanomaterial with controllable morphology, stable structure, and excellent catalytic performance, as well as its preparation method and a water remediation method based on this composite material for efficient degradation of quinolone antibiotics. This application constructs two morphologies of Sm2O3 nanomaterials—rod-like and granular—and coordinates the redox active component of Co3O4 with the dispersed and stabilizing component of Al2O3 to build a multi-interface synergistic catalytic system. This solves the problems of weak activation ability of persulfate, poor environmental adaptability, and low degradation efficiency of traditional single oxide catalysts, achieving broad-spectrum, rapid, and wide-environmental-condition remediation of quinolone antibiotic-contaminated water.
[0009] Several alternative methods are provided below, but they are not intended as additional limitations on the overall solution above. They are merely further additions or optimizations. Provided there are no technical or logical contradictions, each alternative method can be combined individually with respect to the overall solution above, or multiple alternative methods can be combined with each other.
[0010] In step (1): This invention first uses a hydrothermal method to prepare one-dimensional Sm2O3 nanorods (Sm2O3-NR): Specifically, 8.0 g of samarium nitrate was completely dissolved in 360 mL of deionized water. Under vigorous stirring, 10 wt% NaOH aqueous solution was slowly added dropwise to adjust the pH of the system to 12. The mixture was stirred continuously for 30 min to obtain a uniform suspension. The suspension was placed in a Teflon-lined autoclave and hydrothermally reacted at 180 ℃ for 12 h. After cooling, the suspension was washed until neutral, dried at 60 ℃ for 12 h, and calcined at 500 ℃ for 4 h to obtain Sm2O3 nanorod supports with regular structure and uniform aspect ratio.
[0011] This invention also employs an oxalic acid co-precipitation method to prepare zero-dimensional Sm2O3 nanoparticles (Sm2O3-NP): Specifically, 8.0 g of samarium nitrate was dissolved in 360 mL of deionized water, and oxalic acid aqueous solution was slowly added dropwise while stirring continuously for 30 min. After centrifugation, washing, and drying, the mixture was calcined at 500 ℃ for 4 h to obtain Sm2O3 nanoparticle carriers with uniform particle size and large specific surface area.
[0012] In step (2): Optionally, the Sm2O3-NR dispersion or Sm2O3-NP dispersion is an aqueous dispersion with a concentration of 3~6 g / L.
[0013] Optionally, the metal salt solution is an aqueous solution, Co 2+ The ions originate from the dissolution of Co(NO3)2·3H2O, Al 3+ The solution is derived from Al(NO3)3·9H2O. The amount of Co(NO3)2·3H2O used is calculated as 15~18 g / L, and the amount of Al(NO3)3·9H2O used is calculated as 22~25 g / L.
[0014] Optionally, the precipitant is an aqueous solution of Na2CO3 with a concentration of 20~22 g / L.
[0015] Optionally, the volume ratio of the Sm2O3-NR dispersion or Sm2O3-NP dispersion to the metal salt solution and the precipitant is 4:1:1.
[0016] Furthermore, the concentration of the Sm2O3-NR dispersion or Sm2O3-NP dispersion is 5 g / L; the amount of Co(NO3)2·3H2O in the metal salt solution is 17.46 g / L, the amount of Al(NO3)3·9H2O is 23.632 g / L; and the concentration of the Na2CO3 aqueous solution is 21.2 g / L.
[0017] In this step, the present application uses a precise pH-controlled co-precipitation method to in-situ load Co3O4 / Al2O3 composite active components on the surface of two types of Sm2O3 supports. As a specific operation method of the most preferred embodiment, the Sm2O3-NR dispersion or Sm2O3-NP dispersion is obtained by ultrasonically dispersing 1 g of Sm2O3-NR or Sm2O3-NP in 200 mL of ultrapure water; the metal salt solution is obtained by dissolving 0.873 g of Co(NO3)2·3H2O and 1.1816 g of Al(NO3)3·9H2O in 50 mL of deionized water; the precipitant is obtained by dissolving 1.06 g of Na2CO3 in 50 mL of deionized water; the volume ratio of the Sm2O3-NR dispersion or Sm2O3-NP dispersion to the metal salt solution and the precipitant is 200 mL:50 mL:50 mL.
[0018] Preferably, the pH of the reaction system is strictly controlled at 9.0±0.1.
[0019] Optionally, the reaction system is aged in a water bath at 60°C for 3 hours.
[0020] In step (3): Optionally, the drying temperature is 55~60 ℃; the air calcination conditions are: calcination at 350~450 ℃ for 2~4 h in an air atmosphere.
[0021] Furthermore, the drying temperature is 60 ℃, and the drying time is generally more than 12 hours overnight; the air calcination conditions are: air calcination at 400 ℃ for 3 hours.
[0022] This application also provides a nanocomposite catalyst prepared by the preparation method described above.
[0023] This application also provides a method for the degradation of quinolone antibiotics in water, including: The nanocomposite catalyst was redispersed and added to polluted water containing quinolone antibiotics. Persulfate was added to the polluted water at the same time, and the reaction was carried out at natural water temperature. The nanocomposite catalyst activated the persulfate to degrade the quinolone antibiotics.
[0024] First, the nanocomposite catalyst is dispersed in water and ultrasonically treated to obtain a uniform and stable nanocomposite catalyst dispersion. Then, the nanocomposite catalyst dispersion, quinolone antibiotic-contaminated water, and persulfate solution are uniformly mixed. The persulfate solution is efficiently activated by the multi-interface synergistic effect of the nanocomposite catalyst, and the quinolone antibiotics in the water are rapidly oxidized and degraded under mild conditions to achieve water purification and remediation.
[0025] Optionally, the quinolone antibiotic is at least one of enoxacin, norfloxacin, and ciprofloxacin.
[0026] Optionally, the concentration of quinolone antibiotics in the polluted water is 1–20 mg / L; further, the concentration of quinolone antibiotics in the polluted water is 5–15 mg / L.
[0027] Optionally, the pH range of the polluted water is 3.5–11. The nanocomposite catalyst of this application is adaptable to complex actual water environments, including acidic, neutral, and alkaline conditions, and is suitable for complex water systems such as natural surface water and industrial wastewater, exhibiting extremely strong environmental adaptability.
[0028] Optionally, the reaction temperature range under natural water temperature is 15–40 °C; the reaction time is 10–15 min. The nanocomposite catalyst of this application has a degradation reaction temperature of 15–40 °C, can react efficiently under natural water temperature conditions, and the reaction time is only 10–15 min, achieving rapid and efficient degradation and removal of antibiotics.
[0029] Optionally, the mass ratio of the nanocomposite catalyst to the quinolone antibiotic is 10:1 to 1.25:1, and the mass ratio of the nanocomposite catalyst to persulfate is 1:2 to 1:10. This ensures a sufficient supply of active sites and oxidant, balancing degradation efficiency and economy.
[0030] More preferably, the mass ratio of the nanocomposite catalyst to the quinolone antibiotic is 6:1 to 4:1, and the mass ratio of the nanocomposite catalyst to persulfate is 1:4 to 1:8.
[0031] Preferably, the nanocomposite catalyst is Co3O4 / Al2O3 / Sm2O3-NR.
[0032] In addition, this application also provides a method for detecting quinolone antibiotics in water: Samples were analyzed using a high-performance liquid chromatograph equipped with an ultraviolet detector, a temperature-controlled column oven, and an autosampler. Chromatographically pure acetonitrile and ultrapure water were used as experimental solvents. Depending on the acidity or alkalinity of the sample, 0.1% formic acid, 0.025M phosphoric acid, or triethylamine could be added to improve peak shape and suppress peak tailing.
[0033] The chromatographic conditions were as follows: a 4.6 mm × 250 mm, 5 μm C18 column was used; the mobile phase was acetonitrile-0.025 M phosphoric acid aqueous solution (adjusted to pH 3.0 with triethylamine) (13:87, V / V); the detection wavelength was 220 nm or 254 nm; the flow rate was 1.0 mL / min; the column temperature was 30 ℃; the injection volume was 10 μL; isocratic elution was used; and the detection time was 15 min. The standard and the test sample were accurately weighed and prepared into standard and test solutions of appropriate concentrations using matching solvents. After sonication and centrifugation, the solutions were filtered through a 0.22 μm microporous membrane for later use.
[0034] After the instrument is equilibrated for 30 minutes until the baseline is stable, the blank solvent, reference solution and test solution are injected sequentially. Each group is injected in parallel twice. The system suitability requirements are a theoretical plate number of not less than 3000, a tailing factor of 0.9~1.1 and a peak area RSD ≤ 2.0%.
[0035] The content of the target compound in the sample was calculated using the external standard method. The calculation formula is as follows: C 样(供试品) = (A 样 × C 标 ) / A 标 In the formula, A sample: the peak area of the test solution; A-standard: Peak area of the standard solution; Cstandard: The known concentration of the standard solution; C sample: Concentration of the test solution.
[0036] After the detection is completed, rinse the chromatographic system with 90% acetonitrile aqueous solution and seal the chromatographic column with 50% methanol. The chromatographic parameters can be fine-tuned according to the actual separation effect to ensure accurate and stable detection.
[0037] Compared with the prior art, this application has at least one of the following beneficial effects: (1) This application successfully prepared two types of Sm2O3 nanomaterials with controllable morphology: rod-shaped and granular. Combining the advantages of high crystallinity from the hydrothermal method and high specific surface area from the co-precipitation method, the obtained Sm2O3 nanomaterials have stable structures and abundant defect sites. On the one hand, Sm2O3 can provide an excellent supporting substrate for other active components. On the other hand, Sm2O3 also serves as an active component. Through composite modification with Co and Al bimetallic oxides, a rare earth-transition metal multi-component synergistic catalytic interface was constructed, and the synergistic effect among the active components was fully utilized, significantly improving the activation ability of persulfate.
[0038] (2) The preparation process of this application is mild, with precise and controllable parameters and good repeatability. It does not require extreme conditions such as high temperature and high pressure throughout the process. The raw materials are inexpensive and readily available, and the process flow is simple, making it suitable for batch preparation and engineering applications. Through precise pH control and water bath aging process, the aggregation of active components is effectively inhibited, ensuring that Co and Al bimetallic oxides are uniformly dispersed on the surface of Sm2O3 nanomaterials, which significantly improves catalytic stability and cycle life.
[0039] (3) The composite material prepared in this application can work stably under a wide pH range (3.5-11) and a wide temperature range (15-40 °C), and is suitable for complex water systems such as natural surface water and industrial wastewater. It has strong environmental adaptability and breaks through the limitation of traditional catalysts that can only work in a narrow neutral range.
[0040] (4) This application has a fast degradation rate and high processing efficiency. It can achieve efficient degradation of quinolone antibiotics in just 10 to 15 minutes. It has a broad-spectrum degradation effect on norfloxacin, enoxacin and ciprofloxacin. It has no secondary pollution, is green and environmentally friendly, and has extremely high application value and industrialization prospects in the field of antibiotic water pollution treatment.
[0041] (5) The nanocomposite catalyst prepared in this application has good stability. After the system has completed 5 rounds of cyclic degradation reaction, the degradation efficiency of the catalytic system for ciprofloxacin is still maintained at more than 90%, and the catalytic activity has not decreased significantly. Attached Figure Description
[0042] Figure 1 SEM images of the Co3O4 / Al2O3 / Sm2O3-NR materials prepared in Example 1; Figure 2 The graph shows the degradation effects of Sm2O3-NP, Co3O4 / Al2O3 / Sm2O3-NP, Sm2O3-NR, and Co3O4 / Al2O3 / Sm2O3-NR on water containing ciprofloxacin in Example 2. Figure 3 This is a graph showing the degradation effect of different pH values on water containing ciprofloxacin in Example 3; Figure 4 The graph shows the effect of different persulfate (PMS) dosages on the degradation of ciprofloxacin-containing water in Example 4. Figure 5 The graph shows the degradation effect of different concentrations of Co3O4 / Al2O3 / Sm2O3-NR on ciprofloxacin in Example 5. Figure 6 This is a graph showing the degradation effect of Co3O4 / Al2O3 / Sm2O3-NR on water containing different quinolone antibiotics in Example 6; Figure 7This is a graph showing the degradation effect of Co3O4 / Al2O3 / Sm2O3-NR recycling in Example 7; Figure 8 This is a comparative figure showing the effects of different lanthanide nanomaterials on the degradation of ciprofloxacin, as shown in Comparative Example 1. Detailed Implementation
[0043] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0045] A method for detecting quinolone antibiotics in water: Samples were analyzed using a high-performance liquid chromatograph equipped with an ultraviolet detector, a temperature-controlled column oven, and an autosampler. Chromatographically pure acetonitrile and ultrapure water were used as experimental solvents. Depending on the acidity or alkalinity of the sample, 0.1% formic acid, 0.025M phosphoric acid, or triethylamine could be added to improve peak shape and suppress peak tailing.
[0046] The chromatographic conditions were as follows: a 4.6 mm × 250 mm, 5 μm C18 column was used; the mobile phase was acetonitrile-0.025 M phosphoric acid aqueous solution (adjusted to pH 3.0 with triethylamine) (13:87, V / V); the detection wavelength was 220 nm or 254 nm; the flow rate was 1.0 mL / min; the column temperature was 30 ℃; the injection volume was 10 μL; isocratic elution was used; and the detection time was 15 min. The standard and the test sample were accurately weighed and prepared into standard and test solutions of appropriate concentrations using matching solvents. After sonication and centrifugation, the solutions were filtered through a 0.22 μm microporous membrane for later use.
[0047] After the instrument is equilibrated for 30 minutes until the baseline is stable, the blank solvent, reference solution and test solution are injected sequentially. Each group is injected in parallel twice. The system suitability requirements are a theoretical plate number of not less than 3000, a tailing factor of 0.9~1.1 and a peak area RSD ≤ 2.0%.
[0048] The content of the target compound in the sample was calculated using the external standard method. The calculation formula is as follows: C 样(供试品) = (A 样 × C 标 ) / A标 In the formula, A sample: the peak area of the test solution; A-standard: Peak area of the standard solution; Cstandard: The known concentration of the standard solution; C sample: Concentration of the test solution.
[0049] After the detection is completed, rinse the chromatographic system with 90% acetonitrile aqueous solution and seal the chromatographic column with 50% methanol. The chromatographic parameters can be fine-tuned according to the actual separation effect to ensure accurate and stable detection.
[0050] The degradation rate of quinolone antibiotics involved in the following examples is calculated using the following formulas: The degradation rate of quinolone antibiotics = the concentration of quinolone antibiotics after degradation C / the initial concentration of quinolone antibiotics C0 × 100%.
[0051] Example 1: Preparation of supported cobalt oxide catalysts Co3O4 / Al2O3 / Sm2O3-NR or Co3O4 / Al2O3 / Sm2O3-NP Sm2O3-NR can be prepared by the following method: (1) Add 8g of samarium nitrate powder to 360mL of deionized water and stir vigorously.
[0052] (2) Then, slowly add 10wt% NaOH aqueous solution until the pH value reaches 12, and continue stirring for 30 minutes to form a uniform suspension.
[0053] (3) Transfer the mixture to a 100 mL stainless steel autoclave lined with Teflon and heat at 180°C for 12 hours.
[0054] (4) After the precipitate has cooled to room temperature, collect it and wash it repeatedly with deionized water until the pH of the supernatant is neutral.
[0055] (5) The product was dried at 60°C for 12 hours and then calcined at 500°C for 4 hours to obtain Sm2O3-NR nanorods.
[0056] Sm2O3-NP can be prepared by the following method: (6) Dissolve 8.0 g of samarium nitrate completely in 360 mL of deionized water and stir until the system is clear and homogeneous to obtain an aqueous solution of samarium nitrate precursor; (7) Coprecipitation reaction: Under continuous vigorous stirring, slowly add 10wt% oxalic acid aqueous solution to the above samarium nitrate precursor aqueous solution until the precipitation no longer increases. After the addition is completed, continue vigorous stirring for 30 min to allow samarium ions to fully react with oxalic acid and generate samarium oxalate precipitate system. (8) Precipitation separation and purification: The precipitate system obtained from the reaction was centrifuged and the solid precipitate product was collected; the obtained solid precipitate was thoroughly washed to remove residual impurities in the system, and then dried and calcined at 500 °C for 4 h to obtain Sm2O3-NP nanoparticles.
[0057] Preparation of Co3O4 / Al2O3 / Sm2O3-NR or Co3O4 / Al2O3 / Sm2O3-NP nanocomposite catalysts (9) Disperse 1 g of Sm2O3-NR powder obtained in step (5) or Sm2O3-NR / NP powder obtained in step (8) in 200 mL of ultrapure water and sonicate for 30 minutes to achieve uniform dispersion. (10) Prepare an aqueous solution containing Co(NO3)2·3H2O (0.873 g) and Al(NO3)3·9H2O (1.1816 g) in 50 mL of deionized water, i.e., a metal salt solution, while dissolving Na2CO3 (1.06 g) separately in 50 mL of deionized water as a precipitant.
[0058] (11) Under continuous stirring, 50 mL of metal salt solution and 50 mL of precipitant Na2CO3 solution were slowly added dropwise to 200 mL of Sm2O3-NR suspension or 200 mL of Sm2O3-NP suspension, respectively, and the pH value was controlled at 9.0 ± 0.1.
[0059] (12) After the addition is completed, the resulting slurry is aged in a 60°C water bath for 3 hours; then the solid is collected by centrifugation and washed repeatedly with deionized water until the pH of the supernatant reaches about 7.0.
[0060] (13) After drying at 60°C, the obtained precursor was calcined in air at 400°C for 3 hours to obtain Co3O4 / Al2O3 / Sm2O3-NR or Co3O4 / Al2O3 / Sm2O3-NP samples.
[0061] (14) The nanoparticles Sm2O3-NR, Sm2O3-NP, Co3O4 / Al2O3 / Sm2O3-NR, and Co3O4 / Al2O3 / Sm2O3-NP samples obtained in steps (5), (8), and (13) were observed by electron microscopy. Figure 1 ,Depend on Figure 1 The results show that the nanomaterials prepared in Sm2O3-NR and Co3O4 / Al2O3 / Sm2O3-NR have a rod-like structure and a smooth surface. The nanomaterials prepared in Sm2O3-NP and Co3O4 / Al2O3 / Sm2O3-NP have a granular structure and a rough surface.
[0062] Example 2: Effects of different nano-dispersions on the degradation efficiency of ciprofloxacin (1) Add the Sm2O3-NP, Co3O4 / Al2O3 / Sm2O3-NP, Sm2O3-NR and Co3O4 / Al2O3 / Sm2O3-NR prepared in Example 1 to pure water to prepare a mother liquor at a concentration of 500 mg / L and disperse it by ultrasonication for 30 min.
[0063] (2) Persulfate (PMS) was added to the water containing the target pollutant ciprofloxacin. The concentration of ciprofloxacin was 10 mg / L, and the amount of persulfate added was 0.2 g / L. Finally, the Sm2O3-NP, Co3O4 / Al2O3 / Sm2O3-NP, Sm2O3-NR, and Co3O4 / Al2O3 / Sm2O3-NR nano-dispersions prepared in step (1) were added respectively, with the amount added based on a final concentration of 50 mg / L for each nanomaterial. At the same time, a stir bar was added to ensure that the pollutant, oxidant, and catalyst were evenly dispersed. The stirring speed was 200 r / min. Samples were taken at certain time intervals, and methanol was added as a quencher. After filtration, the solution was subjected to high performance liquid chromatography to detect the concentration of the remaining ciprofloxacin.
[0064] The results are as follows Figure 2 As shown in Figure 2, comparing the treatment effects of different nano-dispersions, the Co3O4 / Al2O3 / Sm2O3-NR nanomaterial exhibits the best degradation and remediation ability for ciprofloxacin. Based on the results of this degradation experiment, it can be confirmed that this material possesses excellent pollutant removal efficiency, and the conclusion that this material is adaptable to a wide range of acidic and alkaline water environments will be further supported in subsequent examples. Relying on its excellent degradation performance, this material can be applied to the treatment and remediation of ciprofloxacin pollutants in water bodies.
[0065] Example 3: Effects of different pH conditions on the degradation efficiency of ciprofloxacin The Co3O4 / Al2O3 / Sm2O3-NR prepared in Example 1 was added to pure water to prepare a stock solution at a concentration of 500 mg / L and ultrasonically dispersed for 30 min.
[0066] Persulfate (PMS) was added to water containing the target pollutant ciprofloxacin at a concentration of 10 mg / L. The amount of persulfate added was 0.4 g / L. To explore the suitable pH conditions for the experiment, the pH of the water was adjusted to 3.5, 5, 7, 9, and 11 using HCl and NaOH, respectively. Finally, a Co3O4 / Al2O3 / Sm2O3-NR nano-dispersion was added, with the amount added based on a final concentration of 50 mg / L for Co3O4 / Al2O3 / Sm2O3-NR. A stir bar was added simultaneously to ensure uniform dispersion of the pollutant, oxidant, and Co3O4 / Al2O3 / Sm2O3-NR. The stirring speed was 200 r / min. Samples were taken at regular intervals, and methanol was added as a quencher. After filtration, the solutions were analyzed by high-performance liquid chromatography (HPLC) to determine the concentration of residual ciprofloxacin.
[0067] The degradation effect of Co3O4 / Al2O3 / Sm2O3-NR under different pH treatments for 10 min is as follows: Figure 3 As shown, from Figure 3 It can be seen that the degradation rate of Co3O4 / Al2O3 / Sm2O3-NR nanoparticles within 10 min is 80-97% under different pH conditions. This indicates that Co3O4 / Al2O3 / Sm2O3-NR nanoparticles are suitable for degrading ciprofloxacin under a wide range of acidic and alkaline environments, thereby completing the remediation of polluted water sources.
[0068] Example 4: Effects of different persulfate dosages on the degradation efficiency of ciprofloxacin The Co3O4 / Al2O3 / Sm2O3-NR prepared in Example 1 was added to pure water to prepare a stock solution at a concentration of 500 mg / L and ultrasonically dispersed for 30 min.
[0069] Persulfate (PMS) was added to water containing the target pollutant ciprofloxacin at a concentration of 10 mg / L. The persulfate dosages were 0.05, 0.1, 0.2, 0.4, 0.6, and 0.8 g / L. Finally, a Co3O4 / Al2O3 / Sm2O3-NR nano-dispersion was added, with the addition amount based on a final Co3O4 / Al2O3 / Sm2O3-NR concentration of 50 mg / L. A stir bar was added simultaneously to ensure uniform dispersion of the pollutant, oxidant, and Co3O4 / Al2O3 / Sm2O3-NR at a stirring speed of 200 rpm. Samples were taken at regular time intervals, and methanol was added as a quencher. After filtration, the solutions were analyzed by high-performance liquid chromatography (HPLC) to determine the concentration of remaining ciprofloxacin.
[0070] The effects of adding different doses of persulfate on the treatment of ciprofloxacin are as follows: Figure 4 As shown, from Figure 4It can be seen that the degradation rate increases with the increase of persulfate dosage. When the amount of sulfate added is 0.6~0.8 g / L, the degradation of antibiotics is completed in only about 10 minutes. However, it was also found that after a certain amount of persulfate is added, its effect becomes saturated. Excessive persulfate does not have a significant promoting effect on the degradation of ciprofloxacin. Considering all factors, the optimal dosage of persulfate is 0.2 mg / L.
[0071] Example 5: Degradation effect of different concentrations of Co3O4 / Al2O3 / Sm2O3-NR on ciprofloxacin The Co3O4 / Al2O3 / Sm2O3-NR prepared in Example 1 was added to pure water to prepare a stock solution at a concentration of 500 mg / L and ultrasonically dispersed for 30 min.
[0072] Co3O4 / Al2O3 / Sm2O3-NR was added to the water containing the target pollutant ciprofloxacin at a concentration of 10 mg / L. The amounts of Co3O4 / Al2O3 / Sm2O3-NR added, based on the final concentrations of Co3O4 / Al2O3 / Sm2O3-NR, were 12.5, 25, 50, 75, and 100 mg / L, respectively. Finally, PMS was added at a concentration of 0.2 g / L. A stir bar was added simultaneously to ensure uniform dispersion of the pollutant, oxidant, and Co3O4 / Al2O3 / Sm2O3-NR at a stirring speed of 200 r / min. Samples were taken at regular intervals, and methanol was added as a quencher. After filtration, the solutions were analyzed by high-performance liquid chromatography (HPLC) to determine the concentration of remaining ciprofloxacin.
[0073] The effects of adding different dosages of Co3O4 / Al2O3 / Sm2O3-NR nanocomposite catalyst on the treatment of ciprofloxacin are as follows: Figure 5 As shown. From Figure 5 It can be seen that after a certain amount of Co3O4 / Al2O3 / Sm2O3-NR is added, its effect becomes saturated. Excessive Co3O4 / Al2O3 / Sm2O3-NR will not have a significant promoting effect on the degradation of ciprofloxacin. Considering all factors, the optimal amount of nanocomposite catalyst is 50 mg / L.
[0074] Example 6: Effects of Co3O4 / Al2O3 / Sm2O3-NR on the degradation efficiency of different quinolone antibiotics The target pollutants norfloxacin, ciprofloxacin, and enoxacin were added to the water body at a concentration of 10 mg / L. Persulfate (PMS) was added at 0.2 g / L. Finally, a Co3O4 / Al2O3 / Sm2O3-NR nanorod dispersion was added, with the amount added based on a final concentration of 50 mg / L for Co3O4 / Al2O3 / Sm2O3-NR. A stir bar was added to ensure uniform dispersion of the pollutants, oxidant, and Co3O4 / Al2O3 / Sm2O3-NR at a stirring speed of 200 r / min. Samples were taken at regular time intervals, and methanol was added as a quencher. After filtration, the solutions were analyzed by high-performance liquid chromatography (HPLC) to determine the concentration of remaining quinolones.
[0075] Treatment effects of different quinolone antibiotics on water bodies Figure 6 As shown. From Figure 6 It can be seen that the Co3O4 / Al2O3 / Sm2O3-NR / PMS system has a degradation and remediation effect on the three types of quinolone-contaminated water bodies, and the degradation rate reaches almost 100% after 20 min, indicating that Co3O4 / Al2O3 / Sm2O3-NR has a good remediation effect on quinolone antibiotic-contaminated water bodies.
[0076] Example 7: Stability study of Co3O4 / Al2O3 / Sm2O3-NR: The Co3O4 / Al2O3 / Sm2O3-NR composite material prepared in Example 1 was used, and the Co3O4 / Al2O3 / Sm2O3-NR / PMS catalytic system was constructed according to Example 2. Multiple cyclic degradation experiments were carried out to evaluate the cyclic stability and structural durability of the catalytic material.
[0077] After each catalytic degradation reaction, the solid Co3O4 / Al2O3 / Sm2O3-NR catalyst was recovered by centrifugation, cleaned, and dried before being put into a new round of ciprofloxacin degradation cycle testing. Experimental results are as follows: Figure 7 As shown, the results indicate that after the system completed five consecutive cycles of degradation reaction, the degradation efficiency of ciprofloxacin by the catalytic system remained above 90%, and the catalytic activity did not decrease significantly.
[0078] The above-mentioned cyclic test results prove that the Co3O4 / Al2O3 / Sm2O3-NR material prepared in this application has a stable chemical structure and excellent catalytic durability. This catalytic material can be recycled and reused multiple times, and has the value and feasibility for large-scale application in actual water treatment engineering.
[0079] Comparative Example 1: Effects of different lanthanide nanomaterials on the degradation efficiency of ciprofloxacin Following the preparation method of Example 1, Co3O4 / Al2O3 / La2O3-NR / NP and Co3O4 / Al2O3 / Ce2O4-NR / NP composite materials were successfully prepared by replacing samarium nitrate with lanthanum nitrate and cerium nitrate, respectively. Furthermore, according to the experimental procedure of Example 2, the two materials were used for the degradation treatment of ciprofloxacin-contaminated water, and the experimental results are as follows. Figure 8 As shown.
[0080] Figure 8 The results showed that within a 30-minute reaction time, only the samarium oxide-based composite material achieved 100% degradation of ciprofloxacin, while the other two rare earth oxide composite materials failed to achieve complete degradation. This demonstrates that samarium oxide does not merely act as an inert carrier in the system; rather, it synergistically participates with Co3O4 / Al2O3 in the degradation reaction of ciprofloxacin, playing a crucial role in improving the pollutant degradation performance of the materials.
[0081] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.
Claims
1. A method for degrading quinolone antibiotics in water, characterized in that, include: The nanocomposite catalyst was redispersed and added to polluted water containing quinolone antibiotics. Persulfate was added to the polluted water at the same time, and the reaction was carried out at natural water temperature. The nanocomposite catalyst activated the persulfate to degrade the quinolone antibiotics. The preparation method of the nanocomposite catalyst includes: (1) Sm2O3 nanorods Sm2O3-NR were prepared by hydrothermal method or Sm2O3 nanoparticles Sm2O3-NP were prepared by oxalic acid coprecipitation method; (2) The obtained Sm2O3-NR or Sm2O3-NP was redispersed in water to obtain Sm2O3-NR dispersion or Sm2O3-NP dispersion, respectively; the precipitant and the substance containing Co were also redispersed in water. 2+ Ions and Al 3+ The metal salt solution of the ion was simultaneously added dropwise to the Sm2O3-NR dispersion or the Sm2O3-NP dispersion, and the pH of the reaction system was controlled to be 8.5~9.
5. After the addition was completed, the reaction system was aged in a water bath at 55~65℃ for 2~4 hours. (3) The reaction system after aging is centrifuged, washed with water until neutral, and dried in sequence, and then calcined in air to obtain nanocomposite catalysts Co3O4 / Al2O3 / Sm2O3-NR or Co3O4 / Al2O3 / Sm2O3-NP.
2. The method according to claim 1, characterized in that, In step (2): Both the Sm2O3-NR dispersion and the Sm2O3-NP dispersion are aqueous dispersions with a concentration of 3~6 g / L. The metal salt solution is an aqueous solution, Co 2+ The ions originate from the dissolution of Co(NO3)2·3H2O, Al 3+ The amount of Co(NO3)2·3H2O used is calculated as 15~18 g / L, and the amount of Al(NO3)3·9H2O used is calculated as 22~25 g / L. The precipitant is an aqueous solution of Na2CO3 with a concentration of 20~22g / L; The volume ratio of the Sm2O3-NR dispersion or Sm2O3-NP dispersion to the metal salt solution and the precipitant is 4:1:1; The pH of the reaction system was controlled at 9.0 ± 0.
1.
3. The method according to claim 1, characterized in that, In step (3), the drying temperature is 55~60 ℃; the air calcination conditions are: calcination at 350~450 ℃ for 2~4 h in an air atmosphere.
4. The method according to claim 1, characterized in that, The quinolone antibiotic is at least one of enoxacin, norfloxacin, and ciprofloxacin; the concentration of the quinolone antibiotic in the polluted water is 1–20 mg / L.
5. The method according to claim 1, characterized in that, The pH range of the polluted water is 3.5 to 11.
6. The method according to claim 1, characterized in that, The reaction temperature range under natural water temperature is 15–40℃; the reaction time is 10–15 min.
7. The method according to claim 1, characterized in that, The mass ratio of the nanocomposite catalyst to the quinolone antibiotic is 10:1 to 1.25:1, and the mass ratio of the nanocomposite catalyst to persulfate is 1:2 to 1:
10.
8. The method according to claim 1, characterized in that, The nanocomposite catalyst is Co3O4 / Al2O3 / Sm2O3-NR.
Citation Information
Patent Citations
Supported cobaltosic oxide catalyst, and preparation method and application thereof
CN104014340A
